PENGARUH KINERJA KEUANGAN TERHADAP PERUBAHAN LABA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA - Susanti, Indiska Dwi Nury; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Financial statement of the company is a description of the condition of a company which includes financialposition and the achievements which have been obtained by the company are reflected in the financial statement.Various analysis instruments can be applied to process financial statement and one of the analysis instrumentsis financial ratio analysis. The purpose of this research is to find out the influence of current ratio, debt to totalasset ratio, total asset turnover, and return on assets to the changes in profit. The samples are pharmaceuticalcompanies which are listed in Indonesia Stock Exchange and these companies have been selected by usingpurposive sampling. The data is the financial statement from 2011 to 2014. The analysis technique has been doneby using multiple linear regression analysis, F test, and t test. Based on the result of the research, it has beenfound that current ratio has significant and positive influence since its regression coefficient value is 0.731 and ttest significance value is smaller than 0.05 that is 0.024. Debt to total asset ratio has positive and insignificantinfluence since its regression coefficient value is 0.498 and t test significance value is larger than 0.05 that is0.581. Total asset turnover has positive and significant influence since its regression coefficient is 1.014 and ttest significance value is smaller than 0.05 that is 0.024. Return On Asset has negative and insignificantinfluence since its regression coefficient is -1.629 and t test significance value is larger than 0.05 that is 0.382.Keywords: Current Ratio, Debt to Total Asset Ratio, Total Asset Turnover, Return on Assets, Changes in Profit